Pengaruh Model Problem Based Learning berbantuan Geogebra terhadap Kemampuan Numerasi Peserta Didik Kelas IV Sekolah Dasar - Masykur , Muhammad; Eka, Sastrawati; Alirmansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the level of effectiveness of the Geogebraassisted Problem Based Learning Model on the Numeracy Ability of Class IV Elementary School Students. This research was conducted at SD Negeri 036/I Kilangan in the odd semester of the 2024/2025 academic year. This type of research is Pre-Experimental Designs using a quantitative approach. The research design used in this research is OneGroup Pretest-Posttest Design. Data collection techniques were obtained by observing the implementation of educators' and students' activities and giving essay test questions to students. Then the data is processed by comparing the results before giving the action (pretest) with the results after giving the action (posttest). The research results showed that there was a significant difference between the average initial ability score before being given treatment using the Geogebraassisted PBL model, namely 65.70 and the final average ability value after being treated with the Geogebra-assisted PBL model, namely 85.38. Based on the results of hypothesis testing using the T-test, a sig value was obtained. (2-tailed) is smaller than 0.05, namely 0.005, then Ho is rejected and Ha is accepted, and the N-Gain result is 0.59 so that the effectiveness of increasing students' numeracy skills is categorized as moderate. The conclusion of this research shows that the Problem Based Learning model assisted by Geogebra is quite effective on the numeracy abilities of class IV elementary school students.